THE CONSTITUTIONALLY OF THE DPR’SSUPERVISORY FUNCTION OVER CONSTITUTIONAL COURT JUSTICE AND INDEPENDENT INSTITUTION - Avany Mahmudah; Radian Salman; Mohammad Syaiful Aris (Qaumiyyah: Jurnal Hukum Tata Negara, 2025)
The constitutionality of the DPR's supervisory authority over Constitutional Court judges and independent state institutions raises serious problems in the Indonesian constitutional system, especially after the ratification of Article 228A of DPR Regulation Number 1 of 2025 concerning Amendments to DPR RI Regulation Number 1 of 2020 concerning Rules of Procedure. This provision grants the DPR the authority to evaluate officials it previously nominated, with evaluations deemed binding. However, such authority lacks a legal foundation in either the 1945 Constitution or the MD3 Law, rendering it potentially ultra vires and contrary to the principle of Separation of Powers and judicial independence. The removal of Constitutional Court Justice Aswanto illustrates a clear example of legislative interference and politicization of the judiciary. Similar threats extend to independent institutions such as the Corruption Eradication Commission (KPK) and the Judicial Commission (KY), both of which require functional and institutional autonomy. This study employs a normative legal method. Findings confirm that Article 228A poses a constitutional threat and should be repealed to restore institutional equilibrium. Legal reform and regulatory safeguards are urgently needed to protect the integrity and independence of judicial and independent bodies within Indonesia’s democratic rule of law framework. Abstrak Konstitusionalitas kewenangan pengawasan DPR terhadap Hakim Mahkamah Konstitusi dan lembaga negara independen menimbulkan persoalan serius dalam sistem ketatanegaraan Indonesia, terutama pasca disahkannya Pasal 228A Peraturan DPR Nomor 1 Tahun 2025 tentang Perubahan Atas Peraturan DPR RI Nomor 1 Tahun 2020 tentang Tata Tertib. Pasal ini memberikan kewenangan evaluatif terhadap pejabat negara yang diangkat atas usul DPR, dengan hasil yang bersifat mengikat. Ketentuan tersebut tidak memiliki dasar konstitusional dalam UUD 1945 maupun dasar legal dalam Undang-Undang tentang Majelis Permusyawaratan Rakyat, Dewan Perwakilan Rakyat, Dewan Perwakilan Daerah, dan Dewan Perwakilan Rakyat Daerah (UU MD3), sehingga berpotensi melampaui kewenangan yang sah (ultra vires) dan mencederai prinsip pemisahan kekuasaan serta independensi kekuasaan kehakiman. Kasus pemanggilan dan pemberhentian Hakim Konstitusi Aswanto menunjukkan bukti konkret politisasi dan intervensi legislatif terhadap lembaga yudikatif. Evaluasi yang bersifat mengikat ini juga berpotensi diterapkan terhadap lembaga independen seperti KPK dan KY, yang semestinya bebas dari tekanan politik. Penelitian ini menggunakan pendekatan hukum normatif. Hasil analisis menunjukkan bahwa Pasal 228A harus ditinjau ulang dan dihapus, karena berpotensi merusak sistem checks and balances dan menggeser hubungan antarlembaga negara menjadi subordinatif. Reformasi peraturan dan penguatan jaminan independensi lembaga yudikatif dan lembaga negara independen menjadi langkah penting menjaga prinsip negara hukum yang demokratis.